Reformulation Of Business Competition Law Enforcement Based On A Hybrid Model - Habibi, Habibi (Prophetic Law Review, 2021)
Private enforcement in business competition law enforcement has several weaknesses rendering it sub-optimal in its compensation function. This article proposes a reformulation of business competition law enforcement based on a hybrid model for enhancing private law. This article uses a normative method with laws and regulation, cases, and a conceptual approach: law materials in the form of laws and regulations and Business Competition Supervisory Commission and court judgements are analyzed using hybrid theory so the weaknesses of business competition law enforcement can be identified, then, the result of a reformation proposal can be obtained by evaluating the result of analysis which are presented argumentatively. The result of this research study shows that a privately triggered public enforcement pattern which is implemented in private enforcement cannot work as compensation function optimally. The weakness in regulating private enforcement has created many obstacles for the appellant of trade damage. It is necessary to reformulate the business competition law enforcement in the future by enhancing private enforcement. The enforcement is conducted by facilitating the claimants with diverse features which ease them to get compensation for the trade damage they suffer.Keywords: Private enforcement; public enforcement; hybrid modeling; competition lawReformulasi Penegakan Hukum Persaingan Usaha Berbasis Model HibridaAbstrakPenegakan hukum perdata dalam penegakan hukum persaingan usaha memiliki beberapa kelemahan sehingga fungsi kompensasinya kurang optimal. Artikel ini mengusulkan reformulasi penegakan hukum persaingan usaha berdasarkan model hibrida untuk menyempurnakan hukum perdata. Artikel ini menggunakan metode normatif dengan pendekatan peraturan perundang-undangan, kasus, dan konseptual: bahan hukum berupa peraturan perundang-undangan dan peraturan Komisi Pengawas Persaingan Usaha serta putusan pengadilan dianalisis menggunakan teori hibrida sehingga kelemahan penegakan hukum persaingan usaha dapat diidentifikasi, maka, hasil usulan reformasi dapat diperoleh dengan mengevaluasi hasil analisis yang disajikan secara argumentatif. Hasil penelitian ini menunjukkan bahwa pola penegakan publik yang dipicu oleh hal-hal keperdataan yang diterapkan dalam penegakan hukum perdata tidak dapat memberikan fungsi kompensasi secara optimal. Kelemahan dalam mengatur penegakan hukum perdata telah menciptakan banyak hambatan bagi pemohon gugatan kerugian dalam hubungan keperdataan. Ke depan, perlu dirumuskan kembali penegakan hukum persaingan usaha dengan meningkatkan penegakan hukum perdata. Penegakan tersebut dilakukan dengan memfasilitasi penggugat dengan beragam fitur yang memudahkan mereka untuk mendapatkan kompensasi atas kerugian yang mereka derita.Kata Kunci: Penegakan privat; penegakan publik; model hibrida; hukum persaingan usaha